La identidad étnica no corresponde necesariamente a la reivindicación indígena. Expresiones identitarias de los teenek y nahuas en la Huasteca veracruzana - Anath Ariel de Vidas (Nuevo mundo - Mundos Nuevos, 2007)
Ethnic Identity and Ethnic Political Activity Don’t Necessarily Go Hand in Hand.  Identitary Expressions Among the Teenek and Nahua of the Veracruzan Huasteca.In the Huasteca region, in Mexico’s northeast, two Indians groups, the Nahua and the Teenek, experience the interaction with cultural otherness and with modern, national society in very different ways.  This paper compares the Teenek position toward the Other to the one of their nearby Nahua neighbors.  While the Teenek position is more reserved and hermetic, the Nahua position toward the Other is characterized by more active and assertive participation outside their communities.  The cultural strategies of both groups appear to be radically opposed.  Nonetheless, none of these two groups is involved in Indian political militancy and their ethnic identity is expressed in more discrete ways.  The comparison between the two groups help us understand the character of the differentiated interactions of two neighboring ethnic groups with the modern world and national society that may be rooted in each group’s particular worldview and history.  From a theoretical standpoint, this paper addresses the problem of the cultural and social construction of collective identities and Otherness in modern and multicultural societies, proposing to reconstruct the concept of ethnicity from a cognitive perspective rather than as identity politics.